2011
DOI: 10.1074/jbc.m110.214726
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an in Vitro Interaction between an Insect Immune Suppressor Protein (CrV2) and Gα Proteins

Abstract: The protein CrV2 is encoded by a polydnavirus integrated into the genome of the endoparasitoid Cotesia rubecula (Hymenoptera:Braconidae:Microgastrinae) and is expressed in host larvae with other gene products of the polydnavirus to allow successful development of the parasitoid. CrV2 expression has previously been associated with immune suppression, although the molecular basis for this was not known. Here, we have used time-resolved Förster resonance energy transfer (TR-FRET) to demonstrate high affinity bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Several of these genes were also related to factors in eukaryotic signaling pathways, which suggested they were virulence factors that caused some of the physiological alterations that occur in parasitized hosts. Subsequent studies supported this by demonstrating experimentally how certain BV and IV gene products interact with host immune molecules or cells (Beck and Strand, 2005; Thoetkiattikul et al, 2005; Beck and Strand, 2007; Ibrahim and Kim, 2008; Labropoulou et al, 2008; Kwon and Kim, 2008; Cooper et al, 2011; Magkrioti et al, 2011; Bitra et al, 2012; Gueguen et al, 2013), while implicating other genes in altering host growth, metabolism or endocrine physiology (Provost et al, 2004; Falabella et al, 2006; Kim et al, 2013; Presad et al, 2013). …”
Section: Mid-2000s: Sequencing the Dnas In Particles Further Muddy Thmentioning
confidence: 95%
“…Several of these genes were also related to factors in eukaryotic signaling pathways, which suggested they were virulence factors that caused some of the physiological alterations that occur in parasitized hosts. Subsequent studies supported this by demonstrating experimentally how certain BV and IV gene products interact with host immune molecules or cells (Beck and Strand, 2005; Thoetkiattikul et al, 2005; Beck and Strand, 2007; Ibrahim and Kim, 2008; Labropoulou et al, 2008; Kwon and Kim, 2008; Cooper et al, 2011; Magkrioti et al, 2011; Bitra et al, 2012; Gueguen et al, 2013), while implicating other genes in altering host growth, metabolism or endocrine physiology (Provost et al, 2004; Falabella et al, 2006; Kim et al, 2013; Presad et al, 2013). …”
Section: Mid-2000s: Sequencing the Dnas In Particles Further Muddy Thmentioning
confidence: 95%
“…The studies of species more suitable for microscopy will certainly facilitate such measurements. It is noteworthy that FRET imaging has been achieved in zebrafish (Fan et al, 2007;Tao et al, 2011) as well as Drosophila melanogaster (Lissandron et al, 2007;Shafer et al, 2008;Gervasi et al, 2010;Cooper et al, 2011), and the latter studies have helped to elucidate the role of adenylyl cyclases and cAMP in learning processes in the D. melanogaster brain.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for the latter came from studies showing that most genes on DNAs in virions are transcribed in hosts but are not transcribed in wasps (Rasoolizadeh et al, 2009;Bitra et al, 2011;Provost et al, 2011;Burke and Strand, 2012b;Chevignon et al, 2014;Dorémus et al, 2014;Bitra et al, 2015). Experimental studies also showed that genes/ microRNAs in BV or IV virions disrupt specific host immune defences against wasp offspring (Beck and Strand, 2005;Thoetkiattikul et al,, 2005;Beck and Strand, 2007;Pruijssers and Strand, 2007;Ibrahim and Kim, 2008;Labropoulou et al,, 2008;Kwon and Kim, 2008;Cooper et al, 2011;Magkrioti et al, 2011;Bitra et al, 2012;Gueguen et al, 2013), alter host growth (Provost et al, 2004;Falabella et al, 2006;Pruijssers et al, 2009;Kim et al, 2013;Prasad et al, 2014;Ignesti et al, 2018;Wang et al, 2018), and potentially affect host interactions with food plants and other organisms (Zhu et al, 2018;Tan et al, 2018).…”
Section: Key Insights Into Pdv Evolution and Function Required Genomic Data From Waspsmentioning
confidence: 99%